Ideologi Tokoh Utama (Wanita) dan Tokoh Tambahan dalam Novel Hanum Karya Mustofa W.H. - Putri, Meri Eka; Abdurahman, Abdurahman; Zulfadhli, Zulfadhli (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This studyaimed to describe the ideology off igures concerning the way of life, responsibility, love, truth, and justice, the ideals of the struggle, resistance and strugglein the novel Hanum W Hashim Mustafa's work. The datain this study are sentences or quotations related to indicators of research contained in the novel Hanum W Hashim Mustafa's work. The data source of this research is the novel Hanum W Hashim Mustafa's work. The study's findings area way of life these leaders think of a better life to come and have agreat responsibility to both his brother and relatives. Ideology concerning their loveistight, the characters love each other, so that the figures unite to defend truth and justice and to fight and struggle for their rights as citizens of Indonesia.